Roadmap Consensus on Carotid Artery Plaque Imaging and Impact on Therapy Strategies and Guidelines: An International, Multispecialty, Expert Review and Position Statement - Saba, L.; Brinjikji, W.; Spence, J.D.; Wintermark, M.; Castillo, M.; de Borst, G.J.; Yang, Q.; Yuan, C.; Buckler, A.; Edjlali, M.; Saam, T.; Saloner, D.; et al. (American Journal of Neuroradiology, 2021)
SUMMARY: Current guidelines for primary and secondary prevention of stroke in patients with carotid atherosclerosis are based on the quantification of the degree of stenosis and symptom status. Recent publications have demonstrated that plaque morphology and composition, independent of the degree of stenosis, are important in the risk stratification of carotid atherosclerotic disease. This finding raises the question as to whether current guidelines are adequate or if they should be updated with new evidence, including imaging for plaque phenotyping, risk stratification, and clinical decision-making in addition to the degree of stenosis. To further this discussion, this roadmap consensus article defines the limits of luminal imaging and highlights the current evidence supporting the role of plaque imaging. Furthermore, we identify gaps in current knowledge and suggest steps to generate high-quality evidence, to add relevant information to guidelines currently based on the quantification of stenosis.AHAAmerican Heart AssociationIPHintraplaque hemorrhageLRNClipid-rich necrotic core